A novel process for obtaining smoke-flavoured salmon using water vapour permeable bags. (March 2015) - Rizo, Arantxa; Máñes, Verónica; Fuentes, Ana; Fernández-Segovia, Isabel; Barat, José M.
Highlights: A new smoking–salting process using water vapour permeable (WP) bags is presented. This procedure gives smoke-flavoured salmon with similar traits than a product obtained by a traditional process. The new method reduces processing steps, brine wastes and fish handling. Abstract: We aimed to optimise a new smoking–salting method using water-vapour permeable bags to obtain smoke-flavoured salmon. This involved a smoking–salting process with three salt doses (4, 6, 8 g salt/100 g fresh salmon) and two packaging types: high barrier (HB) bags and water vapour permeable bags (WP) with different humidity levels (50%, 60% and 70% RH). The salting and vacuum packaging combination increased the salt concentration in the final product versus WP bag packaging. The lower the RH for WP-packed samples in the drying chamber, the lower the moisture and aw values. The 8% salt dose/60% RH samples came closer to the aw, salt content and moisture levels determined in commercial samples. In WP samples, 50% and 60% RH completely evaporated the water released by muscle. Sensory attributes of the new product obtained similar scores to the commercial product. The new methodology is suitable to obtain smoke-flavoured salmon with similar physico-chemical characteristics and consumer acceptance to a commercial smoked salmon reducing processing steps and brine wastes.